2021
DOI: 10.1038/s41598-021-89707-1
|View full text |Cite
|
Sign up to set email alerts
|

12-Hydroxyeicosapentaenoic acid inhibits foam cell formation and ameliorates high-fat diet-induced pathology of atherosclerosis in mice

Abstract: Atherosclerosis is a chronic inflammatory disease associated with macrophage aggregate and transformation into foam cells. In this study, we sought to investigate the impact of dietary intake of ω3 fatty acid on the development of atherosclerosis, and demonstrate the mechanism of action by identifying anti-inflammatory lipid metabolite. Mice were exposed to a high-fat diet (HFD) supplemented with either conventional soybean oil or α-linolenic acid-rich linseed oil. We found that as mice became obese they also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“… 50 Higher concentrations of the EPA-derived HEPEs in mice fed the fish oil diet may well have contributed to the enhanced resolution response as HEPEs have been suggested to have anti-inflammatory and pro-resolving activities. 51 , 52 The lower concentrations of the AA-derived PGs, TBx 2 and HETEs could also contribute to a less pro-inflammatory environment in the fish oil fed mice to ensure proper resolution of the antigen-induced peritonitis. 53 NK cells have been shown to express high levels of 12/15-LOX in a murine model of type I diabetes 22 and could, therefore, be the source of the 12- and 15-HEPEs in the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Higher concentrations of the EPA-derived HEPEs in mice fed the fish oil diet may well have contributed to the enhanced resolution response as HEPEs have been suggested to have anti-inflammatory and pro-resolving activities. 51 , 52 The lower concentrations of the AA-derived PGs, TBx 2 and HETEs could also contribute to a less pro-inflammatory environment in the fish oil fed mice to ensure proper resolution of the antigen-induced peritonitis. 53 NK cells have been shown to express high levels of 12/15-LOX in a murine model of type I diabetes 22 and could, therefore, be the source of the 12- and 15-HEPEs in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For lipidomics, female C57BL/6J wild-type mice (6 weeks old) were purchased from Japan SLC (Hamamatsu, Japan), and were maintained for 2 months on chemically defined diets containing 4% (wt/wt) dietary oil (soybean oil or linseed oil, Oriental Yeast, Tokyo, Japan) 65 in the SPF animal facility at National Institutes of Biomedical Innovation, Health and Nutrition (NIBIOHN; Osaka, Japan). Male GF mice (ICR background), and their control ICR mice (age, 6 weeks) were purchased from Japan SLC (Hamamatsu, Japan); these mice were maintained for 2 months on chemically defined diets containing 4% (wt/wt) dietary oil (soybean oil or linseed oil) under GF or SPF conditions, respectively, at NIBIOHN and Oriental Bioservice, Inc. For contact hypersensitivity studies, female C57BL/6J wild-type mice (age, 7 weeks) were purchased from Japan SLC and maintained for 1 week before use in experiments in the SPF animal facility at NIBIOHN.…”
Section: Methodsmentioning
confidence: 99%
“…For diabetes experiments, male C57BL/6J wild-type mice (age, 8 weeks) were purchased from Japan SLC and CLEA Japan (Tokyo, Japan), and maintained in the SPF animal facility at NIBIOHN for 3–4 months on HFD composed of chemically defined materials. 65 Mice were maintained under conditions (16:8 h light/dark cycle, 22–24 °C, and 50–60% humidity), with ad libitum access to food and distilled water. Mice were euthanized by cervical dislocation under isoflurane (Forane, AbbVie, North Chicago, Illinois, USA) anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, there are certain lipid-derived batokines such as 12-HEPE (12-hydroxyeicosapentaenoic acid) [21] and 12,13-diHOME [48,49] that have been described as mediators of immune cell function and/or inflammation in various other tissues [71][72][73]. For example, 12,13,-diHOME was previously described a pro-inflammatory agent with cytotoxic properties and has also been described as an inhibitor of neutrophil respiratory burst [74,75].…”
Section: Paracrine Batokines: Regulators Of Brown Adipose Tissue Immunitymentioning
confidence: 99%
“…In a more recent study, Levan et al identified that 12,13-diHOME secreted from the gut microbiome has been reported to promote allergic inflammation in neonates and alter lipid uptake in human dendritic cells [72]. Similarly, administration of 12-HEPE resulted in inhibiting the transformation of macrophages to an inflammatory foam cell phenotype [71]. This line of evidence suggests that there might be a physiological role for BAT-derived signaling lipids to modulate circulating immune cell or tissue-specific immune cell function.…”
Section: Paracrine Batokines: Regulators Of Brown Adipose Tissue Immunitymentioning
confidence: 99%